The Impact of Internet on Teaching and Learning of Geography in Secondary Schools in Kabale Municipality. - Kato Brian (Kabale University, 2023)
This research intended to examine the contribution of internet in teaching and learning of geography in Kabale Municipality. It was guided by objectives which were to which were to examine the impact of internet use on teaching and learning in secondary schools in Kabale Municipality, to examine teachers’ and students’ perception on the use of internet in teaching and learning in secondary schools in Kabale Municipality and to identify the challenges associated with the use of internet in in secondary schools in Kabale Municipality. The study adopted a cross sectional survey design and a sample size of 326 respondents was used. Simple random and purposive sampling techniques were used in selecting respondents. Data collection was done using questionnaires and interview guide. Findings of this study established that the intensive use of internet and the process-oriented learning environment supported the development of students’ expertise in internet and enhanced students’ in critical thinking skills, teacher and student intervention and increase students’ learning motivation. Furthermore, internet can offer opportunities to teachers for obtaining educational resources from the internet to enrich course content. The results indicated that majority of teachers involved students in using computers every day. The study established that an increasing number of teachers are embracing integration of internet in teaching and learning geography. However, computers were not adequate for full integration of internet in teaching and learning. This signified low use of these hardware tools. This study established that the major barriers preventing more successful integration of internet in teaching and learning in secondary schools were; lack of internet skills, availability of insufficient number of computers and lack of motivation and confidence. Furthermore, inappropriate teacher training as a major barrier in the integration of internet in teaching and learning. The study recommended that teachers should be given sufficient training on how to use internet in teaching and learning processes to acquire the requisite knowledge and skills in integrating the technology in classrooms. Teachers should also be provided with adequate technological resources, technical support and administrative support to encourage them successfully use internet in teaching and learning. Students should be involved in using internet in learning activities such as doing assignments and searching the internet for learning resources because it is believed that internet can enhance teacher and student interaction and also tends to increase students learning motivations.